Pattern of Anaemia among Non-haematological Malignant Patients in a Tertiary Care Hospital: A Cross-sectional Study - Rishad, Mahbub Mayukh; Jannat, Miftahul; Rakib, Nur mohammad; Sultana, Tania; Reza, Ishrat Binte; Noor, Nawsabah; Afrin, Zafia; Monjurrahman,; Azad, Khan Abul Kalam (Bangladesh Journal of Medicine, 2023)
Background: Anaemia is a frequent complication in cancer patients and has been linked to a reduction in quality of life as well as a poor prognosis. Considering the paucity of dataregarding anaemia in non-haematological carcinoma in developing countries, this studyaimed to evaluate the pattern of anaemia in non-haematological carcinoma patients admitted in a tertiary care hospital of Bangladesh. Methods: This cross-sectional study was conducted over 56 adult anaemic patients of nonhaematological carcinoma inDhaka Medical College Hospital, from 1st of September 2017 to 1stdecember 2017.After getting written informed consent, a detailed history, clinical examination and thorough investigation were carried out in each patient. All the methods in the present study were carried out following the ethical guidelines of the 1975 Declaration of Helsinki.Data were recorded in separated case record form and analyzed by IBM SPSS version 26. Results: The majority of the study participants were male (62.5%), aged >50 years (64.3%), and from rural areas (60.7%). Metastasis affected 50% of the research participants, and colorectal carcinoma (17.9%) was the most common type of non-haematological carcinoma. The majority of patients had moderate to severe (73.2%), hypochromic (62.5%), and microcytic (62.5%) anemia. In contrast to patients without colorectal cancer, those who had it were more likely to get severe anemia (p=0.001). In patients with metastasis, the likelihood of having hemoglobin below 10 g/dL was 11.27 times higher than in patients without metastasis (COR = 11.27; 95% CI 2.23-56.86). Conclusion: Maximum anaemic non-haematogical patients had haemoglobin <10 g/dL with microcytosis and hypochromia. Bangladesh J Medicine 2023; 34(3): 192-198